Study of the N126 dust bubble in the infrared wavelength range - Alimgazinova, N.Sh.; Sharipbay, N.A.; Kyzgarina, M.T.; Manapbayeva, A.B.; Turekhanova, K.M.; Omar, A.Zh.; Demessinova, A.M.; Alibek, A.A. (Recent Contributions to Physics, 2024)
In recent years, the research of bubbles, partially circular structures in the interstellar medium, consisting of dust and gas, has received the considerable attention. The analysis of the structure and evolution of bubbles provides insight into the conditions under which stars and planets form in the interstellar medium. Dust bubbles are inextricably linked with star formation regions and are powerful tools for studying the interaction of young stellar objects with their environment at various stages of evolution. The main goal of this article is to study the region of the N126 dust bubble, search for and identify young stellar objects. Identification of young stellar objects by their fluxes at infrared wavelengths is relatively recent, and identification criteria are still at the stage of improvement. Therefore, in this article, the criteria for identifying young stellar objects were used according to the works of Koenig X.P. (2012), Koenig X. P. & Leisawitz D. V. (2014) and Fischer W.J. (2016), which are based on analysis of WISE observational data in the near- and mid-infrared bands W1 (3.4 μm), W2 (4.6 μm), W3 (12 μm), and W4 (22 μm). The data from the 2MASS and AllWISE catalogs with reliable non-zero fluxes of infrared radiation sources were used in that work. For the researched dust bubble, young stellar objects of class 0 (protostars) and class I were not detected. 4 objects of class II, 1 object of the class of transition disks and 48 objects of class III were identified. Energy distributions in the spectra for class II objects were constructed, which also confirmed their evolutionary status. For all identified YSOs, color diagrams were constructed showing the locations of the found objects with their corresponding areas of evolution. Maps of the distribution of YSOs in space are analyzed, which indicate possible signs of an initiated star formation process in the N126 dust bubble.